Comparison of Bichectomy Techniques Through a Clinical Case and 6-Month Follow-up: Six Months of Bichectomy Follow-up - de Sena, Yasmin Rabelo Batalha; Rabêlo-Júnior, Paulo Maria Santos; Gonçalves, Leticia Machado; Lago, Andrea Dias Neves (Journal of Lasers in Medical Sciences, 2022)
Introduction: Bichectomy consists of the partial removal of the Bichat ball (BB) of its buccal extension and smoothing the facial contour. The objective of this study is to present, by means of a clinical case, bichectomy surgery with the use of a high-power diode laser and cold scalpel on different sides of the same patient, analyzing the trans-surgical phase and the pain and edema like consequence operative of each technique and 6-month follow-up. Case Presentation: A 20-year-old female patient reported the occurrence of involuntary trauma to the cheek mucosa and rounded facial appearance. After anamnesis and clinical examination, bichectomy was proposed. For comparison, on the right side, an incision was made using a laser, while on the left side, with a cold scalpel. To assess and measure the progression of treatment, photographs and facial measurements were repeated before the procedure, 7, 14, and 28 days after the procedure, and 2, 3, and 6 months after the procedure. Conclusion: The high-power diode laser showed excellent applicability for bichectomy due to its hemostatic properties in the trans-surgical phase. In addition, it promoted greater patient comfort, with less edema and pain on the side of the face where it was used. DOI:10.34172/jlms.2022.02